2017
DOI: 10.1097/scs.0000000000003499
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Reconstruction Using Autologous Bone and Methylmethacrilate

Abstract: Our study suggests that the material used for reconstruction of calvaria influences the infection rate only in large and complicated defects. Considering the importance of the reconstruction, further studies should explore and confirm the role of material type on the rate of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, when the infection rates were compared based on CP size, the infection rates were 2% for bone and 13.9% for PMMA with skull defects >70 cm 2 , which was significantly different, but in defects <70 cm 2 , there was no significant difference in infection rates indicating graft material has a greater impact on large skull defects, in which case PMMA may be contraindicated. 7 Other results found no significant difference in infection rates between PMMA and AB for all CP patients, as well as the subset of patients with TBI. 20,50 When considering the risks and benefits associated with autografts versus HA implants, both autografts and HA prosthetics have osteogenic potential promoting their integration with the surrounding bone.…”
Section: Comparisons To Consider When Choosing a Cranial Graft Materialsmentioning
confidence: 87%
See 1 more Smart Citation
“…However, when the infection rates were compared based on CP size, the infection rates were 2% for bone and 13.9% for PMMA with skull defects >70 cm 2 , which was significantly different, but in defects <70 cm 2 , there was no significant difference in infection rates indicating graft material has a greater impact on large skull defects, in which case PMMA may be contraindicated. 7 Other results found no significant difference in infection rates between PMMA and AB for all CP patients, as well as the subset of patients with TBI. 20,50 When considering the risks and benefits associated with autografts versus HA implants, both autografts and HA prosthetics have osteogenic potential promoting their integration with the surrounding bone.…”
Section: Comparisons To Consider When Choosing a Cranial Graft Materialsmentioning
confidence: 87%
“…1,4 Infection and graft resorption are the most common complications associated with CP. [5][6][7] The cause of the high complication rates with CP is complex and multifactorial with both patient-and surgery-specific factors contributing to varying extents in different cases. The graft material used for CP is a potential factor contributing to the variance in complication rates, but data in the literature regarding the influence of graft material on post-CP outcomes are inconsistent making it difficult to determine if, when, and to what extent the choice of graft material impacts the rate of perioperative complications.…”
Section: Introductionmentioning
confidence: 99%
“… 8 9 Cranial reconstructive surgery done using MMA has higher rates of infection and wound-healing disorders. 10 11 Study of the long-term consequences of MMA usage for cranioplasty found a 23% complication rate within 8 years of operation. 12 Another study demonstrated that MMA has a high infection rate of 12.7% compared with other materials and is similar to autologous flaps.…”
Section: Introductionmentioning
confidence: 99%